Let's walk our talk: from the July 2015 Financing for Development Conference in Addis Ababa, Ethiopia, down the Road to Dignity by 2030 - Inge Kaul; Donald Blondin (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
In a few months' time, the international community will meet in Addis Ababa, Ethiopia, for the third International Conference on Financing for Development (FfD). The Conference is expected to decide on the means of implementation (MOI) for the Post-2015 Agenda, which will be considered for adoption in September 2015, as well as those for the climate agreement to be reached at the 21st session of the Conference of the Parties (COP21) in Paris in December 2015. However, negotiations on the MOI have so far generated mainly declarations of intent – i.e. statements on what should ideally be done – as opposed to concrete commitments. Moreover, these declarations of intent are basically just requests for 'more'; for instance, more domestic resources, more private investments, more official development assistance (ODA). The MOI declarations that have been put forth to date are no match for the sense of urgency and ambition that marks the Post-2015 Agenda or that which is likely to mark the COP21 outcome document. Thus, the FfD Conference confronts a twofold challenge: closing the 'specificity gap' by moving from declarations of intent to concrete, actionable MOI commitments; and closing the 'ambition gap' by identifying the MOI issues that are of strategic relevance to the successful implementation of the Post-2015 Agenda. To successfully address these two gaps, a key complicating factor will need to be taken into account: the Post-2015 Agenda is setting out to achieve sustainable development goals (SDGs) of universal applicability at a time when the world is undergoing several foundational transformation processes. Accordingly, this paper aims to identify feasible ways and means of narrowing the identified gaps. It does so with a special focus on the national and international public finance side of the challenge. The principal suggestion is a three-step process that could be completed at the forthcoming FfD Conference and repeated at future review meetings. In the first step, the criteria for identifying the MOI issues of high strategic relevance would be determined. These, of course, may vary as the implementation of the respective outcome documents progresses. In Step II, the focus would be on identifying qualifying MOI issues. And in Step III, the decision would be taken to establish operationalization task forces (OTFs) for each of the identified topics. In this way it would be possible to ensure that the goals of ending poverty, transforming all lives and protecting the planet, shift from paper to reality – as we, the international community, 'walk our talk' along the road to dignity and, let us hope, beyond.
Keywords: 330; Agenda 2030; Entwicklungsfinanzierung und öffentliche Finanzen